Replication Data for: Association between circulating inflammatory proteins and temporomandibular disorders: Insight from a two-sample Mendelian randomization analysis - Jiang, Feng (2024)
This dataset supports the findings presented in the study titled "Association between Circulating Inflammatory Proteins and Temporomandibular Disorders: Insight from a Two-Sample Mendelian Randomization Analysis." The dataset comprises results from two-sample Mendelian randomization analyses, examining causal relationships between circulating inflammatory protein levels (exposure) and susceptibility to temporomandibular disorders (TMDs, outcome).